Novel Treatment Options in Patients with Maturity-Onset Diabetes of the Young - Müssig, Karsten (Experimental and Clinical Endocrinology & Diabetes, 2024)
Maturity-onset diabetes of the young (MODY) is the most common monogenetic form of diabetes with an autosomal dominant inheritance pattern. MODY is caused by mutations in genes important for the development and function of pancreatic beta cells, resulting in impaired insulin secretion capacity. To date, 14 different types have been described. While glucokinase (GCK)-MODY (formerly MODY-2) generally requires no drug therapy, other forms of MODY, such as hepatocyte nuclear factor-1-alpha (HNF1A)-MODY (formerly MODY-3) and HNF4A (formerly MODY-1), usually respond very well to sulfonylurea therapy. However, these MODY forms are characterised by a progressive course, meaning that insulin therapy is often required as the disease progresses. Both sulfonylurea therapy and insulin therapy are associated with an increased risk of hypoglycaemia and frequent weight gain. Newer blood glucose-lowering therapies, such as SGLT2 inhibitors (SGLT2i), DPP-4 inhibitors (DPP4i) and GLP-1 receptor agonists (GLP-1RA), have a much lower risk of hypoglycaemia and usually have a favourable effect on body weight. This review aims to provide an overview of the treatment of MODY patients with SGLT2i, DPP4i and GLP-1RA on the basis of previously published clinical studies, case series and case reports.
Keywords: MODY; SGLT2 inhibitor; gliflozin; DPP-4 inhibitor; gliptin; GLP-1 receptor agonist; GLP-1 analogue